(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines a system of exercises aimed at improving students’ monologue speech when teaching complex syntactic wholes (CSH). Particular attention is paid to the relationship between language and speech skills, the role of students’ native language, and mechanisms for overcoming interference. The proposed methodological model is based on the principles of step-by-step instruction, communicativeness, and reliance on the typical structure of CSH. Analysis shows that systematic work with microtext, modeling syntactic relationships, sentence transformation, and reconstruction of semantic blocks significantly improve the quality of monologue speech. The presented exercises are aimed at developing students’ skills in the semantic organization of text, logical coherence, and grammatical accuracy, which contributes to the mastery of productive types of speech and the development of coherent utterance skills.